Integrating justice-based tax education in Pancasila education: Strategies, challenges, and future directions towards fiscal independence in Indonesia - Sari, Chandra Dewi Puspita; Sulistiyono, Adi -; Handayani, I Gusti Ayu Ketut Rachmi (LPMPP Universitas Negeri Yogyakarta, 2025)
The present study aims to investigate the integration of justice-based tax education within the Pancasila Education curriculum, with particular attention to strategies, challenges, and future directions for achieving fiscal independence in Indonesia. Adopting a mixed-methods survey design, the research combined quantitative and qualitative techniques to obtain an in-depth understanding of the phenomenon. Specifically, data were collected from students enrolled in Pancasila Education courses at Universitas Negeri Yogyakarta during the even semester of 2023. The sample was selected using a proportionate stratified random sampling technique, which stratified the Faculty of Engineering, Faculty of Mathematics and Natural Sciences, and Faculty of Vocational Studies, to ensure adequate representation across academic disciplines. The results indicate that implementing justice-based tax education constitutes a critical component of Pancasila Education. Triangulation of data from various approaches reinforced the findings that the main challenges included low awareness of the importance of taxes among students and the general public, as well as difficulties in implementing a curriculum relevant to justice values in tax education. The study recommended several strategic measures, including the development of an inclusive tax education infrastructure, comprehensive training for Pancasila education teachers, refinement of the Pancasila education curriculum to better integrate tax justice aspects, and cross-sector collaboration to ensure the success of such integration. Continuous evaluation of justice-based tax education within Pancasila Education is also emphasised as essential to ensuring the sustainability and effectiveness of this program in increasing public understanding and participation in a fair and sustainable tax system.